2014
DOI: 10.1139/cjfr-2013-0379
|View full text |Cite
|
Sign up to set email alerts
|

Modeling genetic effects on growth of diverse provenances and families of loblolly pine across optimum and deficient nutrient regimes

Abstract: Optimal deployment of improved loblolly pine (Pinus taeda L.) planting stock in the southeastern United States requires knowing how diverse seed sources and families perform over time across the wide range of sites used for plantations. This study tests if the relative growth performance of provenances and families is the same at the individual-tree and stand levels for family block plantings and determines what type of adjustment may be required to account for genetic differences when modeling growth and yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…where Y is the yield of a characteristic of interest (e.g., height, diameter, volume, or basal area; see, e.g., Smith et al 2014) at age A; a is the asymptotic parameter, which represents the asymptotic maximum size of the organism; b is the rate parameter, which represents the intrinsic growth rate; c is the shape parameter, which is related to the power exponent of assimilation; and ε is a normally distributed zero-expectation random error due to observation of the total growth at age A (Richards 1959). Models of unimproved stands simulated using Eq.…”
Section: Illustrating Essential Concepts Using the Heightage Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…where Y is the yield of a characteristic of interest (e.g., height, diameter, volume, or basal area; see, e.g., Smith et al 2014) at age A; a is the asymptotic parameter, which represents the asymptotic maximum size of the organism; b is the rate parameter, which represents the intrinsic growth rate; c is the shape parameter, which is related to the power exponent of assimilation; and ε is a normally distributed zero-expectation random error due to observation of the total growth at age A (Richards 1959). Models of unimproved stands simulated using Eq.…”
Section: Illustrating Essential Concepts Using the Heightage Relationshipmentioning
confidence: 99%
“…In addition to genetic factors, the parameters of stand growth and yield models are influenced by environmental factors that may exhibit different spatial characteristics, such as soil attributes (including soil fertility, texture, moisture, and depth), climate, topography, and wind exposure (Smith et al 2014). Phenotypic responses of genotypes in different environments are distinct, resulting in differences in stand growth patterns (Fu et al 1999;Silva et al 2001;Baltunis et al 2010;Rohner et al 2018).…”
Section: Other Factors Affecting Growth and Yield Models Of Genetically Improved Standsmentioning
confidence: 99%
“…For instance, Colbert et al [9] compared four different functions and indicated that the Chapman-Richards function was prominent. To date, two studies employed a similar approach to compare the differences in growth among provenances [10,11]. Both studies were carried out in the early stages of stand development: at 11 and 14 years old.…”
Section: Introductionmentioning
confidence: 99%